A Prototype Mechatronic Device for Upper Limb Rehabilitation and Analysis of Its Functionality - Jacek S. Tutak; Jacek Mucha (Applied Sciences, 2025)
A prototype device was developed as a simple yet effective tool for the rehabilitation of individuals with upper limb paresis resulting from stroke. The primary objective of the design process was to create a portable rehabilitation device that could be remotely controlled by a therapist via a Bluetooth protocol. The device enables the execution of upper limb rehabilitation exercises and integrates essential modules for assessment, reporting, and user feedback (biofeedback). It comprises a base and three movable arms, each fitted with a container at its distal end. The central arm, positioned at the midpoint of the device’s housing, holds a storage container from which specific objects are retrieved by the user. This arm features an adjustable reach. The remaining two arms are equipped with task-specific containers mounted at their ends. The conceptual framework is based on the execution of various tasks displayed on a screen. The user retrieves objects from the central storage unit and places them into either the left or right container, as indicated. The target container is highlighted both visually on the screen and via an illuminated LED indicator. Pre-programmed sequences for object retrieval and placement are presented on the display, offering clear guidance for the correct positioning and ordering of blocks within the designated containers. The device includes 12 dedicated blocks varying in shape, colour, material, and texture. A mechatronic control system governs the container positioning and arm inclination, enabling a precise adjustment of range of movement according to the exercise’s requirements. A dedicated software system has also been developed for control and management. Functional testing of the prototype was conducted to assess the device’s effectiveness and practical applicability in rehabilitation settings.